Does the academic education of Italian teachers working in early childhood education and care include public health? An analysis of Italian university programmes - Vacchi, Olivia Giulia Bianca; Favero, Beatrice; Driutti, Marco; Zanon, Francesca; Romanese, Federico; Arnoldo, Luca; Brusaferro, Silvio; Brunelli, Laura (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Early childhood education and care (ECEC) is crucial for children's early awareness of well-being and prevention concepts, which are essential for a future healthy lifestyle. Therefore, as public health agents, teachers and educators in ECEC should be taught core topics related to public health and well-being.We investigated the presence and characteristics of public health courses (MEDS-24/B) in Italian primary education sciences Master's programmes in the academic year 2023-24 and propose a model for public health topics to be covered, based on the WHO Essential Public Health Functions.Only a small proportion of the Master's programmes in primary education sciences (n.14/38; 38%) included the course 'General and applied hygiene’ (MEDS-24/B). We found no statistically significant differences in attendance according to any of the variables analysed (i.e. geographical location of the university, size, or public/private status of the university). While topics like ”infectious disease prevention and immunization” were covered in >75%,  others like “oral hygiene” were not covered at all. Detailed analysis showed great heterogeneity at national level in the topics covered between primary education sciences Master's programmes.The current suboptimal presence and coherence of the public health course within the Master's degree in primary education sciences at national level affects the competencies of ECEC educators and teachers, which in turn affects their ability to implement health promotion, disease prevention, and control measures in primary education and the wider community. At national level, more attention should be paid to the academic education of all public health agents.